a + b + c a 2 + b 2 + c 2 = d
Let a , b , c , d be distinct digits between 1 and 9 inclusively, satisfying the equation above. What is the sum of all possible values of d ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
From the given equation, it is clear that a + b + c ∣ a 2 + b 2 + c 2 . Hence, a 2 + b 2 + c 2 ≡ 0 ( m o d a + b + c ) .
And ( a + b + c ) 2 ≡ ( a 2 + b 2 + c 2 ) + 2 ( a b + b c + c a ) ≡ 0 ( m o d a + b + c ) .
If a 2 + b 2 + c 2 ≡ 0 ( m o d a + b + c ) , then 2 ( a b + b c + c a ) ≡ 0 ( m o d a + b + c ) .
Then 2 ( ( a + b ) ( b + c ) − b 2 ) ≡ 2 ( ( − c ) ( − a ) − b 2 ) ≡ 2 ( a c − b 2 ) ≡ 0 ( m o d a + b + c ) .
Therefore, if b 2 = a c , the equivalence will be true, and from all the digit squares, here are the possibilities:
2 2 = 1 ⋅ 4 . Thus, 1 + 2 + 4 1 2 + 2 2 + 4 2 = 7 2 1 = 3 .
3 2 = 1 ⋅ 9 . Thus, 1 + 3 + 9 1 2 + 3 2 + 9 2 = 1 3 9 1 = 7 .
4 2 = 2 ⋅ 8 . Thus, 2 + 4 + 8 2 2 + 4 2 + 8 2 = 1 4 8 4 = 6 .
6 2 = 4 ⋅ 9 . Thus, 4 + 6 + 9 4 2 + 6 2 + 9 2 = 1 9 1 3 3 = 7 .
Now we have explored the most obvious solutions, but are there more?
Since b ≡ − a − c ( m o d a + b + c ) , then b 2 ≡ ( a + c ) 2 ( m o d a + b + c ) .
Hence, 2 ( a c − b 2 ) ≡ 2 ( a c − ( a + c ) 2 ) ≡ 2 ( a 2 + a c + c 2 ) ≡ 0 ( m o d a + b + c ) .
Then 2 ( c − a ) ( a 2 + a c + c 2 ) ≡ 2 ( c 3 − a 3 ) ≡ 0 ( m o d a + b + c ) .
Similarly, with the terms alternated, we will have 2 ( c 3 − b 3 ) ≡ 2 ( b 3 − a 3 ) ≡ 0 ( m o d a + b + c ) .
For generality, let us have a < b < c . This way, we will attempt to find the middle digit for all possible square summation by checking the upper or the lower bound from that number.
Then the case of b = 2 is already checked as shown in the above solution.
For b = 3 , we will have a = 2 left, and 2 ( 3 3 − 2 3 ) ≡ 2 ⋅ 1 9 ≡ 0 ( m o d 2 + 3 + c ) . Then c must be 1 4 to make the equivalence true, but it's not the desired digit, according to the problem.
And we have the triple a = 1 , b = 3 , and c = 9 as shown in the above solution.
Then for b = 4 , if a = 1 , 2 ( 4 3 − 1 3 ) ≡ 1 2 6 ≡ 2 ⋅ 3 ⋅ 3 ⋅ 7 ≡ 0 ( m o d 1 + 4 + c ) . Then c can be 4 or 9 , but if we want all distinct digits, only 9 applies: 1 + 4 + 9 1 2 + 4 2 + 9 2 = 1 4 9 8 = 7 .
And we have the triple a = 2 , b = 4 , and c = 8 as shown in the above solution.
For b = 4 , if a = 3 , 2 ( 4 3 − 3 3 ) ≡ 2 ⋅ 3 7 ≡ 0 ( m o d 1 + 4 + c ) . Then c must be 3 2 , which is not applicable.
For b = 5 , if a = 1 , 2 ( 5 3 − 1 3 ) ≡ 2 ⋅ 1 2 4 ≡ 8 ⋅ 3 1 ≡ 0 ( m o d 1 + 5 + c ) . Only 2 or 2 5 works for c here, but 2 only works for c = 4 as shown above, and 2 5 is not applicable.
For b = 5 , if a = 2 , 2 ( 5 3 − 2 3 ) ≡ 2 ⋅ 1 1 7 ≡ 2 ⋅ 3 ⋅ 3 ⋅ 1 3 ≡ 0 ( m o d 2 + 5 + c ) . Only 2 or 6 works for c , but if we want the distinct digit, only 6 applies: 2 + 5 + 6 2 2 + 5 2 + 6 2 = 1 3 6 5 = 5 .
Unfortunately, it's not a distinct quotient digit, so not a new solution for us.
For b = 5 , if a = 3 , 2 ( 5 3 − 3 3 ) ≡ 2 ⋅ 9 8 ≡ 2 ⋅ 2 ⋅ 7 ⋅ 7 ≡ 0 ( m o d 3 + 5 + c ) . Only 6 applies for c : 3 + 5 + 6 3 2 + 5 2 + 6 2 = 1 4 7 0 = 5 . Again, it's not a distinct quotient digit, so not a new solution for us.
For b = 5 , if a = 4 , 2 ( 5 3 − 4 3 ) ≡ 2 ⋅ 6 1 ≡ 0 ( m o d 4 + 5 + c ) . No digit c exists for this case.
For b = 6 , if c = 7 , 2 ( 7 3 − 6 3 ) ≡ 2 ⋅ 1 2 7 ≡ 0 ( m o d a + 6 + 7 ) . No digit a exists for this case.
For b = 6 , if c = 8 , 2 ( 8 3 − 6 3 ) ≡ 2 ⋅ 2 9 6 ≡ 2 ⋅ 2 ⋅ 2 ⋅ 7 4 ≡ 0 ( m o d a + 6 + 8 ) . No digit a exists for this case.
And we have the triple a = 4 , b = 6 , and c = 9 as shown in the above solution.
For b = 7 , if c = 8 , 2 ( 8 3 − 7 3 ) ≡ 2 ⋅ 1 6 9 ≡ 2 ⋅ 1 3 ⋅ 1 3 ≡ 0 ( m o d a + 7 + 8 ) . No digit a exists for this case.
For b = 7 , if c = 9 , 2 ( 9 3 − 7 3 ) ≡ 2 ⋅ 3 8 6 ≡ 2 ⋅ 2 ⋅ 1 9 3 ≡ 0 ( m o d a + 7 + 9 ) . No digit a exists for this case.
For b = 8 , if c = 9 , 2 ( 9 3 − 8 3 ) ≡ 2 ⋅ 2 1 7 ≡ 2 ⋅ 7 ⋅ 3 1 ≡ 0 ( m o d a + 8 + 9 ) . No digit a exists for this case.
Thus, we can conclude that the only solution ( a , b , c ) are: ( 1 , 2 , 4 ) ; ( 1 , 3 , 9 ) ; ( 1 , 4 , 9 ) ; ( 2 , 4 , 8 ) ; and ( 4 , 6 , 9 ) .
And the only applicable quotient digits include: 3 , 6 , & 7 .
Finally, the sum of all possible d is 3 + 6 + 7 = 1 6 .
you missed (3,6,9) which is also a valid solution ;)
Oops,Now your other problem won't work you have to change the clues
Log in to reply
Oh, I'll change the content a bit then. Thanks.
WLOG a<b<c. Used brute force to arrive at d=(3,5,6,7) but with 5, b=5. So we are left with 3+6+7=16.
Note that the values I have used for (a,b,c) are, keeping a, and b same let c=b+1 to 9. Next b=b+1, till b=9. THEN a=a+1, and repeat till (7,8,9).
(1,2,3)........(1,2,9)-------------7
(1,3,4).......(1,3,9)-------------6
.
.
(1,8,9)--------------------------1
(2,3,4,)......(1,3,9)--------------6
. .
(2,8,9)---------------------------1
.
.
(7,8,9)-------------------------1
{(1+....7)+(1+....6)}+{(1+....5)+(1+....4)}+{(1+....3)+(1+2)}+(1)=\(7^2+5^2+3^2+1^2=84=7*4*(4-1)
trials. ......
I
n
t
e
r
e
s
t
i
n
g
R
e
s
u
l
t
.
once we get d as integer for some a, b and c, no need to take c to 9. Next star with b=b+1, and with new b, c=b+1.
Problem Loading...
Note Loading...
Set Loading...
By completing the squares, the given equation can be rewritten as
a 2 + b 2 + c 2 = d ( a + b + c ) ⟹ a 2 − d a + b 2 − d b + c 2 − d c = 0 ⟹
( a − 2 d ) 2 + ( b − 2 d ) 2 + ( c − 2 d ) 2 = 3 × 4 d 2 ⟹ ( 2 a − d ) 2 + ( 2 b − d ) 2 + ( 2 c − d ) 2 = 3 d 2 .
So we need to look for 3 perfect squares, (keeping in mind that we could have squares of negative numbers), that sum to 3 d 2 for d = 1 , 2 , . . . , 9 . Without loss of generality suppose a < b < c . Now we can then have at most two of the perfect squares being the same, where either 2 a − d = − ( 2 b − d ) , 2 b − d = − ( 2 c − d ) or 2 a − d = − ( 2 c − d ) , (we cannot have all of the perfect squares the same as that would require 2 of a , b , c to be equal to one another). We then proceed to look at the 9 cases separately:
d = 1 ⟹ 3 d 2 = 3 ; the only possibility here is ( 2 a − d ) 2 , ( 2 b − d ) 2 , ( 2 c − d ) 2 = ( 1 , 1 , 1 ) , which we can't have for reasons discussed above, so d = 1 is not possible;
d = 2 ⟹ 3 d 2 = 1 2 ; no combination (with up to 1 repeat) of 1 , 4 , 9 add to 1 2 , so d = 2 ;
d = 3 ⟹ 3 d 2 = 2 7 ; ( 1 , 1 , 2 5 ) works, which gives us ( a , b , c ) = ( 1 , 2 , 4 ) , and thus d = 3 is possible;
d = 4 ⟹ 3 d 2 = 4 8 ; no combination (with up to 1 repeat) of 1 , 4 , 9 , 1 6 , 2 5 , 3 6 add to 4 8 , so d = 4 ;
d = 5 ⟹ 3 d 2 = 7 5 ; the only possibility for the squares used is ( 1 , 2 5 , 4 9 ) , which could be generated by either ( a , b , c ) = ( 2 , 5 , 6 ) or ( 3 , 5 , 6 ) , for which b = d , and so d = 5 ;
d = 6 ⟹ 3 d 2 = 1 0 8 ; the squares ( 4 , 4 , 1 0 0 ) follow from ( a , b , c ) = ( 2 , 4 , 8 ) , so d = 6 is possible;
d = 7 ⟹ 3 d 2 = 1 4 7 ; the squares ( 1 , 2 5 , 1 2 1 ) follow from ( a , b , c ) = ( 4 , 6 , 9 ) , so d = 7 is possible:
d = 8 ⟹ 3 d 2 = 1 9 2 ; one of the squares used must be one of 8 1 , 1 0 0 , 1 2 1 , 1 4 4 or 1 6 9 , but as none of 1 1 1 , 9 2 , 7 1 , 4 8 or 2 3 is the sum of two squares we see that d = 8 ;
d = 9 ⟹ 3 d 2 = 2 4 3 ; the only possibility for the squares used is ( 1 , 1 2 1 , 1 2 1 ) , but this would require that b , c be ( − 1 , 1 0 ) , which is not allowed, so d = 9 .
The only possible values for d are thus 3 , 6 , 7 , their sum being 1 6 .
Note: While some brute force is used here, there are a limited number of squares to work with so the casework only took about 5 minutes, and thus I felt my approach was still worth sharing.